2023
DOI: 10.1002/chem.202301061
|View full text |Cite
|
Sign up to set email alerts
|

Sugar‐Bridged Fullerene Dumbbells and Their Interaction with the [10]Cycloparaphenylene Nanoring

Abstract: The synthesis and characterization of four dumbbell‐shaped fullerene molecules connected by isosorbide and isomannide moieties is presented. Additionally, their electrochemical behavior and their ability to form complexes with [10]cycloparaphenylene ([10]CPP) were investigated. The cyclic voltammetry (CV) results of the fullerene dumbbells demonstrate a high electron affinity, indicating their strong interaction with electron‐donating counterparts such as carbon nanorings, which possess complementary charge an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Due to the challenges in precisely estimating the solubility of intensely coloured compounds, the solubility of 14 was assessed using UV-Vis spectroscopy as a representative of the other compounds since they only differ in the stereochemistry of the sugar addend. 35 The results indicated that 14 is soluble in toluene at concentrations of 60 mg mL −1 . The significance of this property of furan-fused fullerenes lies in their potential applications and their amenability to processing in material chemistry.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Due to the challenges in precisely estimating the solubility of intensely coloured compounds, the solubility of 14 was assessed using UV-Vis spectroscopy as a representative of the other compounds since they only differ in the stereochemistry of the sugar addend. 35 The results indicated that 14 is soluble in toluene at concentrations of 60 mg mL −1 . The significance of this property of furan-fused fullerenes lies in their potential applications and their amenability to processing in material chemistry.…”
Section: Resultsmentioning
confidence: 96%
“…In a recent paper, we presented the synthesis of furan-fused fullerenes using a simple reaction protocol for oxidative cycloaddition reaction between medium chain β-keto esters and C 60 in the presence of DBU and 2,2,6,6-tetramethylpiperidine-1-oxy (TEMPO) in toluene for 45 minutes at room temperature. 34,35 The resulting procedure was now used to synthesize fullerene-sugar adducts 13 , 14 , and 15 , which were obtained in yields ranging from 49% to 60%.…”
Section: Resultsmentioning
confidence: 99%